ANALISIS BENTUK TINDAK TUTUR LOKUSI, ILOKUSI DAN PERLOKUSI DALAM NOVEL YANG FANA ADALAH WAKTU KARYA SAPARDI DJOKO DAMONO DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA - Ananda Aura Sifa; I Nyoman Adi Susrawan; I Komang Widana Putra (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2022)
This study discusses the study of pragmatics seen from the aspect of speech acts. This purpose is to determine the locutionary, illocutionary and perlocutionary speech acts, the factors causing the use of locutionary, illocutionary and perlocutionary speech acts in the novel Yang Fana Adalah Waktu by Sapardi Djoko Damono and their implications in the literary learning process. Data collection methods in this study are reading, taking notes and literature study. Data analysis methods are reducing data, presenting data and verifying and concluding data. The results of the speech act research in the novel Yang Fana Adalah Waktu by Sapardi Djoko Damono there are fifty-two utterances including twelve locutionary speech acts, namely seven statement locutions, four question locutions, one command locution. There were twenty-six illocutionary speech acts, including six assertive illocutions, eight directive illocutions, three expressive illocutions, six commissive illocutions, and three declarative illocutions. The perlocutionary speech act in the novel Yang Fana Adalah Waktu by Sapardi Djoko Damono contains fourteen utterances including eight verbal perlocutions, four nonverbal perlocutions, two nonverbal verbal perlocutions. The factors causing the use of locutionary, illocutionary and perlocutionary speech acts include showing promise or ability, flattery or praise, conveying intent and showing prohibition. The implications of the results of the research on locutionary, illocutionary and perlocutionary speech acts in the novel Yang Fana Adalah Waktu in the process of learning literature as in language learning and literary learning are interrelated. The implications of speech act data results in the novel involve the text and allow something meaningful and in reading it is important to have imagination